ON THE USE OF GILLIAN ROSE - Lloyd, Vincent (Heythrop journal, 2007)
Three recent attempts to draw resources for theology from the work of philosopher and social theorist Gillian Rose are examined. Although her work has received little attention, it has been influential in the development of ‘Radical Orthodoxy’. Yet her dense style has led to many misunderstandings of her work. Each of the three attempts to draw theological resources from her work examined is problematic, either because it misrepresents Rose's work or because it reads Rose too narrowly. The outline of a positive account of Rose's philosophy is developed through critical engagements with these three readers. I suggest that an alternative theological appropriation of Rose that focuses on her account of the theological virtues, particularly faith and love, might be possible.